Sustainable earthworks: Optimization with the ICOM method. (November 2020) - Villar, Yago; Menéndez, Marta; Fernández, Zulima; Bernardo, Antonio
Abstract: In the construction of highways and roads, one of the main activities is earthworks. This activity has an economic and environmental impact that cannot be overlooked. The classic method, based on the use of mass diagram models and optimization, does not take into account the type and quality of the material found on site, making it difficult to optimize the actual flow of each material. The ICOM method (Intelligent Method of Optimized Mass Compensation) allows the optimization of classic works such as excavations and fillings resulting in the optimization of operating costs. This versatile method contemplates different options for each project and allows choosing the most appropriate one taking into account, among other factors, the distance travelled by each type of material, which translates into the amount of CO2 emitted and waste generated. This is why the use of the iCom method will enable us to make the work sustainable, while reducing environmental pollution and the amount of waste. This article compares the results obtained by applying the ICOM method with those that can be obtained with the classic method for twenty-four work projects in Spain and Portugal. The results analysed show that the ICOM method achieves a significant reduction in financial costs between 5% and 14.1% and a shortening of the time needed to carry out the work. The method also obtains a reduction in CO2 emissions (between 5.1% and 14%), while generating a smaller volume of waste materials, which implies a reduction in environmental impact. Furthermore, this method provides the reports, plans and diagrams necessary for the complete definition of the earthworks to be carried out